Evaluation of microencapsulated squid oil as a substitute for live microalgae fed to Pacific oyster (Crassostrea gigas) spat - Knauer, J; Southgate, Paul C (National Shellfisheries Association, Inc., 1997)
The potential of gelatin-acacia microcapsules (GAM) containing squid oil as a replacement for a diet of live microalgae (LMA) consisting of a 1:1 mixture of Chaetoceros muelleri and T-ISO was assessed for Pacific oyster (Crassostrea gigas) spat. Shell length, dry weight, and ash-free dry weight (AFDW) of spat was negatively correlated with the dietary level of GAM after 28 days. However, shell length, dry weight, and AFDW of spat fed 80% LMA plus 20% GAM were not significantly different from those of spat fed a 100% LMA ration. Furthermore, the nutritional value of GAM was indicated by the significantly higher AFDW of spat fed 80% LMA plus 20% GAM and 60% LMA plus 40% GAM compared with that of spat fed the same LMA ration without GAM supplementation. When 40 and 60% of LMA were replaced by GAM, the increases in AFDW of spat were 89 and 77% that of those fed 100% LMA, respectively. The AFDW of spat fed the 100% GAM diet was significantly higher compared with that of unfed spat. The results show that GAM could potentially replace up to 20% of LMA used in commercial hatcheries without affecting growth rates.